2019
DOI: 10.3389/fimmu.2019.00049
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Pseudomonas aeruginosa Accelerate Intestinal, Extra-Intestinal, and Systemic Inflammatory Responses in Human Microbiota-Associated Mice With Subacute Ileitis

Abstract: The globally rising incidences of multidrug-resistant (MDR) Pseudomonas aeruginosa (Psae) in humans and live-stock animals has prompted the World Health Organization to rate MDR Psae as serious threat for human health. Only little is known, however, regarding factors facilitating gastrointestinal Psae-acquisition by the vertebrate host and subsequently induced inflammatory sequelae. In the present study, we addressed whether subacute ileitis predisposed mice harboring a human gut microbiota for intestinal MDR … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…The development of resistant P. aeruginosa strains is increasing globally due to the overuse of antibiotics [29]. The wide-spread identification of multidrug-resistant P. aeruginosa in humans and live-stock animals has led to the World Health Organization to assess multidrug-resistant P. aeruginosa as global hazard for human health [30].…”
Section: Resultsmentioning
confidence: 99%
“…The development of resistant P. aeruginosa strains is increasing globally due to the overuse of antibiotics [29]. The wide-spread identification of multidrug-resistant P. aeruginosa in humans and live-stock animals has led to the World Health Organization to assess multidrug-resistant P. aeruginosa as global hazard for human health [30].…”
Section: Resultsmentioning
confidence: 99%
“…Pseudomonas aeruginosa is a ubiquitous environmental Gram-negative bacterium. It causes several hospital-acquired infections, such as severe systemic infections, endocarditis, ventilator-associated pneumonia, and urinary tract infections [ 1 , 2 ]. As an opportunistic pathogen, P. aeruginosa successfully causes infections in immunocompromised individuals, patients on mechanical ventilation, elderly people, or patients with comorbidities.…”
Section: Pseudomonas Aeruginosa Pathogenicity and Virulencementioning
confidence: 99%
“…In addition to co-culture infection and direct cytokine exposure, the use of animal models is the standard method to gain information about the entire immune system after intestinal barrier breakdown during enteropathogenic infection (Gölz et al, 2015;von Klitzing et al, 2017;Heimesaat et al, 2019). In our present mouse model of campylobacteriosis, infected secondary abiotic IL-10 −/− mice suffered from acute enterocolitis within one week after infection (Haag et al, 2012), as indicated by bloody diarrhea and wasting.…”
Section: Campylobacter Jejuni Infection In Stimulated Cell Cultures Imentioning
confidence: 85%